Keterlibatan Orang Tua Dan Dampaknya Terhadap Kesiapan Belajar Membaca Siswa Kelas 1 Sd Negeri Puncakmulya - Sofwatunnisa, Najwa Aulia (CV. SINAR HOWUHOWU, 2025)
First-grade education is a crucial phase in developing foundational literacy skills. However, many students begin school without adequate readiness, particularly in recognizing letters and early reading. At SDN Puncakmulya, a significant number of first-grade students were found to struggle with basic reading skills, largely influenced by the level of parental involvement in their early learning experiences. This study aims to explore the influence of parental involvement on students’ reading readiness. Using a qualitative descriptive approach, data were collected through interviews with first-grade teachers and parents, classroom observations, and document analysis. The research was conducted in three cycles, involving collaborative efforts between the researcher and the teacher to implement supportive teaching strategies. Findings indicate that students with active parental support at home show greater progress in recognizing letters and reading simple words. Teaching methods such as multisensory approaches and visual media enhanced students’ interest and learning outcomes. Moreover, consistent collaboration between school and family created a more supportive learning environment. In conclusion, parental involvement significantly contributes to early reading readiness. Students benefit not only from technical literacy support but also from emotional encouragement and structured learning routines at home. Strengthening school-family collaboration is essential to ensure students’ successful transition into formal learning.